Proposal to improve quality management processes support in a higher education institution - Estrella-Egas, Manuel (2014)
The study's primary objective is to generate a proposal to improve the quality of a process as a support in a Higher Education Center, according to the common problems that can be found from the respective diagnosis, and to propose guidelines to improve that process. The study is based on a synthetic and analytic research with a practical focusing, it has been selected three tools to propose the referred guidelines, which are directed to the optimization of the critical process chosen before. The main findings of the study show that Higher Education Centers would benefit by implementing the proposal, in a conscious and generalized focused to quality as a way to raise customer satisfaction (internal and external); The proposal is supported by a quantitative model with the organization as its basic priority, making it improves the quality of its processes. This model involves: brainstorming; the problem tree; applying a quantitative model, SPSS (Statistical Package for the Social Sciences) to analyze the reliability and availability of the survey applied for this research.